Phytochrome Intermediates and Action Spectra for Light Perception by Dry Seeds - Bartley, Michael R. (1984)
It has previously been demonstrated that far-red irradiation of dry Lactuca sativa L. seeds results in inhibition of subsequent germination. Although red has no effect on dry seeds, a red irradiation following a farred irradiation reverses the effect of far-red. This phenomenon is most noticeable in seeds with artificially raised levels of phytochrome in the far-red absorbing form. Qualitatively similar results have been found for the seeds of Plantago major L., Sinapis arvensis L., and Bromus sterilis L. Action spectra studies on Plantago seeds show that the action peaks for promotion and inhibition of germination of hydrated seeds are at 660 and 730 nanometers, respectively. The action spectrum for inhibition of subsequent germination following irradiation of dry seeds is qualitatively and quantitatively similar to that for hydrated seeds, with an action peak at 730 nanometers, indicating absorption by phytochrome in the far-red absorbing form. However, the action spectrum for the reversal of this far-red effect on dry seeds has a broad peak at 680 nanometers and subsidiary peaks at 650 and 600 nanometers. It is proposed that this effect is due to light absorption by the phytochrome intermediate complex meta-Fa, and that the action spectrum reflects the in vivo absorption properties of this intermediate.